Relationship Between Plant Strategy Types and Soil Characteristics in Backdunes and Foredunes - Elmas, Emire; Türkiş, Sevda; Bani, Barış (Springer Science and Business Media LLC, 2024)
Abstract Dune ecosystems support limited plant diversity under harsh conditions. This study examines the distribution of competitor, stress tolerator, and ruderal (CSR) strategies in foredune and backdune areas and their relationships with soil variables. Seasonal variations in soil properties and plant strategy types were assessed using canonical correspondence analysis (CCA) and similarity percentage analysis (SIMPER). The Bray–Curtis similarity index showed a 67% dissimilarity between foredune and backdune plant strategies. Most soil variables exhibited significant seasonal changes (p < 0.05), except phosphorus (P) and calcium carbonate (CaCO3). Competitive and stress-tolerant species were positively associated with pH, salinity, and CaCO3 but negatively correlated with total nitrogen (TN), phosphorus (P), potassium (K), and moisture. In contrast, ruderal and mixed CSR species were linked to higher nutrient levels and moisture. Our findings highlight the adaptive resilience of dune species and the influence of soil conditions on plant community structure. Even without external disturbances, species well-adapted to harsh dune conditions can dominate, illustrating the dynamics of dune succession.
Keywords: Soil; CSR strategies; Dune; Plant functional types; Succession